Perbedaan Rezim HAM dan Rezim Pidana - Radjab, Syamsuddin (Al-Daulah : Journal of Criminal Law and State Administration Law, 2014)
Human Rights is an international private law that put the state as the parties; meaning that the state is obliged to comply with the legal subject of human rights law. As subjects of law, then any violation of human rights has always put the country as the culprit.  Violations  of  human  rights  occurred  when  the  state does not comply with the norms that bind, which is contained in the covenants and international conventions, in which the state has pledged to abide by the process of ratification. Basically, the human rights regime is the relationship between citizens and the State then continue to grow and become international human rights law after the Universal Declaration of 1948 that binds both parties through the base and the base charter agreement. While the criminal regime is a crime (act of crime) which put the individual as a subject of law, and perpetrators can be punished imprisonment. But not all types of crimes can be categorized as a crime of Human Rights, only the gross human rights violations the potential occurrence of crimes against human rights; the crime in question, namely: crimes against humanity, genocide, war crimes and the crime of aggression.